Remediation of Student Errors in Solving Work and Energy Problems Using the Fast Feedback Method - Putri Maulindah; Stepanus Sahala Sitompul; Erwina Oktavianty (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
The study aims to determine the effectiveness of the fast feedback method based on problem-solving according to Polya in remediating student errors in solving work and energy problems at SMP Negeri 4 Dedai. This study is in the form of a pre-experimental study with a one-group pre-test post-test design. The sample of this study consisted of 22 students from class VIII B, which was the experimental class. The data collection tool was a 5-item essay test validated (validity level of 3.6 in the moderate category) and tested for reliability (reliability level of 0.489 in the moderate category). The study results showed an average percentage decrease in student errors in the experimental class of 90.2%. The effectiveness of remediation showed a proportion price of 0.886%. It is hoped that this study can be used as an alternative to student error remediation methods in solving problems on work and energy materials.